Creating Learning Environments Free of Violence in Special Education Through the Dialogic Model of Prevention and Resolution of Conflicts - Duque, Elena; Carbonell, Sara; de Botton, Lena; Roca-Campos, Esther (Frontiers in Psychology, 2021)
Violence suffered by children is a violation of human rights and a global health problem. Children with disabilities are especially vulnerable to violence in the school environment, which has a negative impact on their well-being and health. Students with disabilities educated in special schools have, in addition, more reduced experiences of interaction that may reduce both their opportunities for learning and for building protective social networks of support. This study analyses the transference of evidence-based actions to prevent violence in schools – the dialogic model of prevention and resolution of conflicts (DMPRC) – in the context of a special school, and its impact on the reduction of violence, the creation of egalitarian relationships, and the prevention of bullying. A case study with a communicative approach was conducted including in-depth interviews and communicative focus groups with the diverse participants to analyze the process of transformation carried out in the school and the main actions that give students a voice in the management and creation of egalitarian non-violent relationships. The results show that the inclusion of the students’ voices in the resolution and prevention of conflicts reduces violence, empowers special education students, strengthens friendship relationships, caring behavior, and active positioning among the community. The positive impact of the transference of the DMPRC to special schools contributes to students’ well-being and healthy development by offering safe and protective educational spaces and quality emotional education, also contributing to the achievement of the Sustainable Development Goals related to the elimination of all forms of violence in childhood.